2018
DOI: 10.1523/jneurosci.2164-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Attention Enhances the Efficacy of Communication in V1 Local Circuits

Abstract: Attention is a critical component of visual perception; however, the mechanisms of attention at the granular level are poorly understood. One possible mechanism by which attention modulates neuronal activity is to control the efficacy of communication between connected neurons; however, it is unclear whether attention alters communication efficacy across a variety of neuronal circuits. In parallel, attentional modulation of neuronal firing rate is not uniform but depends upon the match between neuronal feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 41 publications
11
35
0
Order By: Relevance
“…Therefore, this cannot account for the divergent observations between top-down attentional modulations of fMRI and early sensory evoked potentials measured by EEG. Instead, our data are consistent with a recent proposal suggesting spatial attention enhances synaptic efficacy between neurons in the early visual system (Briggs et al, 2013;Hembrook-Short et al, 2019). Such an increase in synaptic efficacy would increase local signaling, which can result in increased broadband LFPs, even at low (or 0%) contrasts.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, this cannot account for the divergent observations between top-down attentional modulations of fMRI and early sensory evoked potentials measured by EEG. Instead, our data are consistent with a recent proposal suggesting spatial attention enhances synaptic efficacy between neurons in the early visual system (Briggs et al, 2013;Hembrook-Short et al, 2019). Such an increase in synaptic efficacy would increase local signaling, which can result in increased broadband LFPs, even at low (or 0%) contrasts.…”
Section: Discussionsupporting
confidence: 92%
“…Spatial attention is hypothesized to act as a spatial filtering ‘in’ mechanism, that enhances the selection of incoming visual stimuli depending on their distance to its focus ( 22, 42, 43 ). This attention-based spatial filtering is often equated with spatial prioritization by cue instruction.…”
Section: Resultsmentioning
confidence: 99%
“…Prior work demonstrated that attention increases the likelihood that a presynaptic input generates a postsynaptic spike among connected pairs of neurons ( Briggs et al. 2013 ; Hembrook-Short et al. 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In both geniculocortical circuits and local circuits within primary visual cortex (V1), attention significantly enhances the likelihood that a presynaptic input gives rise to a postsynaptic spike ( Briggs et al. 2013 ; Hembrook-Short et al. 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation